A novel model predictive control for the single-phase inverter with L type filter in grid-connected mode - Zhang, Zhiming (Nanyang Technological University, 2020)
The energy crisis promotes the research and development of renewable energy grid-connected technologies. The project has made an overall design of the single-phase grid-connected inverter, and each functional module unit has also been introduced in detail. The inverter circuit adopts a single-phase Full-bridge structure as well as analyzes its working state. Proposed a unipolar SPWM with a finite control set model predictive control (FCS-MPC) algorithm control strategy. The single-phase grid-connected inverter adopts the method of voltage source input to control the output current. Through sampling and then FCS-MPC algorithm analysis and prediction, using the cost function to select the minimum duty cycle to control the output current of a single inverter. In the project, each functional module of the single-phase grid-connected inverter and the design method of the specific hardware circuit are given. At the same time, the overall idea of software design is introduced. The entire design algorithm is built on a DSP and is simulated in MATLAB / SIMULINK to verify the practical feasibility of the program. The results demonstrate that the design according to this scheme can make the single-phase grid-connected inverter operate safely, reliably and with a fast dynamic response speed.